Surface pCO2 variability in two contrasting basins of North Indian Ocean using satellite data. (January 2022) - Mohanty, Sachiko; Raman, Mini; Mitra, Debashis; Chauhan, Prakash
Abstract: The spatial and temporal variability of the partial pressure of carbon dioxide (pCO2 ) over the northern tropical Indian Ocean was estimated based on satellite-derived sea surface temperature (SST), sea surface salinity (SSS), and chlorophyll concentration (Chl-a). The distribution of sea surface pCO2 is controlled by various physical processes, such as mixing, entrainment, upwelling, and advection, and by associated biological processes, such as phytoplankton blooms. The results showed lower surface water pCO2 over the Bay of Bengal (BoB) (< 300 μatm) as compared to the Arabian Sea (AS), which could be attributed to low salinity during the northeast monsoon season (December–January) in the BoB. High pCO2 values (> 500 μatm) were found near the Somali coast during the southwest monsoon season (June–August) caused by intense coastal upwelling. The pCO2 over BoB (400–450 μatm) was more than that of the AS in the fall inter-monsoon season (September–November) as a response to the relatively warmer SST over the BoB. The highest spatiotemporal variability of surface pCO2 was observed in the western AS near to the coast and over the northern BoB as a response to the higher variability in biological productivity and salinity, respectively, over these regions. The effect of tropical cyclones on pCO2 variability over the BoB was also assessed in this study. The sea surface pCO2 values were found to be much smaller along the cyclone track after the passage of cyclones because of the strong SST drop and the sudden phytoplankton blooms caused by the entrainment and vertical mixing of subsurface cold and nutrient-rich water with surface water. The cyclone-induced surface cooling and the associated decrease in surface water pCO2 were found to be higher after the passage of the Madi cyclone compared to the Hudhud cyclone. Highlights: The spatiotemporal variability of surface pCO2 in the BoB is dominated by the influx of riverine freshwater. SST and chlorophyll are the decisive factors governing the variability of pCO2 in the AS. Tropical cyclone induced surface cooling and biogeochemical processes, affecting the pCO2 distribution in the BoB.